Estudio de factibilidad para la creación de la empresa Mi Carpintería Arquitectónica S.A.S (2014)
The construction in Colombia is one of the most important and dynamic sectors, due to his great capacity that has to generate of employment, to create added value and to be a multiplier of the economy. On the other hand, factors like the radical transformation in the urban environment of the municipality of Cali, the investment in secondhand housing, or the simple desire of a change in the environment, force the owners to come to designers and builders to remodel and to leave his housings as new. In synthesis, the present study of feasibility to create the company MY ARCHITECTURAL CARPENTRY S.A.S, has developed from the analysis of the socio-economic sector, the market research and the financial projections that were offering the royal information to create this type of company in Cali.